Analysis on dynamic interaction between flexible bodies of large-sized wind turbine and its response to random wind loads. (January 2021) - Guo, Shuangxi; Li, Yilun; Chen, Weimin
Abstract: Analysis of structural dynamic response of wind turbine is one of important issues to assess its structural integrity and safety during operation process. As the output power of wind turbine increasingly gets larger, the structural flexibility of the elastic components, such as rotor blades and supporting tower, of wind turbine gets larger owing to larger structural size, and, consequently, the dynamic interaction between these flexible bodies become more profound or, even, may have a significant impact on the dynamic response of the wind turbine. In this study, the integrated finite element model of a 5-MW wind turbine is developed so as to carry out dynamic response analysis, in terms of both time history and frequency spectrum, of the large wind turbine including multiple elastic bodies and their dynamic interactions. In order to have a deeper insight into the impact and mechanism of the dynamic interaction, the load transmission along its transmitting route and mechanical energy distribution during dynamic response under random wind loads are studied. And, the influences of the stiffness and motion of the supporting tower on the integrated system response are discussed. Our numerical results show that the dynamic interaction between the elastic bodies may be significant during dynamic response. The response of the tower top becomes around 15% larger than that of the simplified model mainly due to the elastic deformation and dynamic vibration (called inertial-elastic effect) of the flexible blade; On the other hand, the elastic deformation may additionally consume around 10% energy (called energy-consuming effect) coming from external wind load, and, consequently, it could decrease the displacement of the tower. Therefore, there is a competition between the energy-consuming effect and inertial-elastic effect of the flexible blade on the overall dynamic response of the wind turbine. As for the blade response, the displacement of the blades gets up to 20% larger than that without blade-tower interaction, because the elastic-dynamic behaviors of the tower principally provides a more flexible and vibrating supporting base, which can significantly change the natural mode shape of the integrated wind turbine and can decrease the natural frequency of the blade. Highlights: Interaction between flexible bodies has a significant impact on structure response. Structural responses become around 15%–20% larger due to dynamic interactions. Coupling mechanism is explained based on load transmission and energy distribution. There's a competition between energy-consuming effect and inertial-elastic effect. Wind load running from the flexible blades to the tower may be amplified.